FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINGKAT PENDAPATAN PEDAGANG KAKI LIMA (STUDI PADA AREA SIMPANG LIMA GUMUL KECAMATAN NGASEM KABUPATEN KEDIRI) - Lutfia Hermida Sari; Arfida Boedirochminarni; M.Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2019)
This research is aimed at analyzing the factors of business location variables, business capital, work experience and working hours on the income level of street vendors, with samples of food and beverage traders in the five intersection area of Ngasem sub-district, Kediri Regency using a simple random sampling technique . In this study using primary data, through questionnaires and direct interviews with traders with 51 respondents. The analytical method used in this study is descriptive quantitative analysis method and multiple linear regression analysis. The results of this study partially the t test (Partial) shows that the business location variable does not have a significant effect with the coefficient sig .0377, business capital has a significant effect on the sig coefficient. 0.007 and working hours have no significant effect with the sig coefficient. 0.299 and simultaneously the f test (simultaneous) produces a significance of 0,000 <0.05 which means that the business location variable (X1), business capital (X2), work experience (X3), and working hours (X4) together have an influence real and positive towards the income level of street vendors in the Kediri Regency five gumul (SLG) intersection area.